PROFIL KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI STATISTIKA DITINJAU DARI KEMAMPUAN RECITING AL QUR’AN - Furkan Furkan (JUPE : Jurnal Pendidikan Mandala, 2022)
This study aims to describe the profile of students' ability to understand mathematical concepts in terms of their ability to recite the Qur'an. This research is a qualitative research with a qualitative - exploratory approach. The research subjects were students of class VIII MTs Al Muthmainnah Soromandi Bima as many as 3 subjects. The research instrument is the researcher himself (main instrument) assisted by a written test and interview guide. The results showed that: (1) high qori' subjects (SQT) had the characteristics of conceptual understanding abilities, namely instrumental and relational understanding; then when answering written test questions and interviews, the results of the answers are neat, systematic, and quick to respond or provide answers when direct interviews are carried out; (2) the subject of moderate qori' (SQS) also has the characteristics of conceptual understanding ability, namely instrumental and relational understanding, then when answering written tests and interviews, the answers are neat, systematic, and quick to provide answers when direct interviews are carried out, although sometimes they stutter. brick; (3) the subject of low qori' (SQR) on the ability to understand concepts has the characteristics of only instrumental understanding, then in answering written questions the answers are not neat, written randomly and are less able to respond to direct interviews